Cobetia sp. Bacteria, Which Are Capable of Utilizing Alginate or Waste Laminaria sp. for Poly(3-Hydroxybutyrate) Synthesis, Isolated From a Marine Environment - Moriya, Hiroki; Takita, Yuto; Matsumoto, Akira; Yamahata, Yuki; Nishimukai, Megumi; Miyazaki, Masao; Shimoi, Hitoshi; Kawai, Sung-Jin; Yamada, Miwa (Frontiers in Bioengineering and Biotechnology, 2020)
We isolated the Cobetia sp. strains IU 180733JP01 (5-11-6-3) and 190790JP01 (5-25-4-2) from seaweeds, and showed that both strains accumulate poly(3-hydroxybutyrate) [P(3HB)] homopolymer in a nitrogen-limiting mineral salt medium containing alginate as a sole carbon source. Genome sequence analysis of the isolated strains showed that they have putative genes which encode enzymes relevant to alginate assimilation and P(3HB) synthesis, and the putative alginate-assimilating genes formed a cluster. Investigation of the optimum culture conditions for high accumulation of P(3HB) showed that when the 5-11-6-3 strain was cultured in a nitrogen-limiting mineral salt medium (pH 5.0) containing 6% NaCl and 3% (w/v) alginate as a sole carbon source for 2 days, the P(3HB) content and P(3HB) production reached 62.1±3.4wt% and 3.11±0.16 g/L, respectively. When the 5-25-4-2 strain was cultured in a nitrogen-limiting mineral salt medium (pH 4.0) containing 5% NaCl and 3% (w/v) alginate for 2 days, the P(3HB) content and P(3HB) productivition reached 56.9±2.1wt% and 2.67±0.11 g/L, respectively. Moreover, the 5-11-6-3 strain also produced P(3HB) in a nitrogen-limiting mineral salt medium (pH 5.0) containing 6% NaCl and freeze-dried and crushed waste Laminaria sp., which is classified into brown algae and contains alginate abundantly. The resulting P(3HB) content and P(3HB) productivity were 13.5±0.13wt% and 3.99±0.15 mg/L/h, respectively. Thus, we demonstrated the potential application of the isolated strains to a simple P(3HB) production process from seaweeds without chemical hydrolysis and enzymatic saccharification.